In Reflection: Media Messaging on Barack Obama and the Black Man$1 (Bs Burdens - Debra C. Smith
This article uses popular mass media to illustrate the Black man$1 (Bs burden regarding the presidential candidacy and subsequent presidency of Barack Obama from 2009 to 2017. It draws on news accounts from November 2008 to January 2009, which vividly depict the burden Black people placed on Barack Obama$1 (Bs presidency and the burden they endured due to his visibility in holding the highest office in the United States. The article$1 (Bs inception resulted from the author$1 (Bs revisiting articles from Newsweek magazine, USA Today, The New York Times, The Washington Post, The Boston Globe, the Miami Herald and other sources saved for years. This process revealed an emerging theme that forms the basis of this article.s